Comparative Effectiveness of Implantable Cardioverter Defibrillators for Primary Prevention in Women. (January 2016) - Zeitler, Emily P.; Hellkamp, Anne S.; Schulte, Phillip J.; Fonarow, Gregg C.; Hernandez, Adrian F.; Peterson, Eric D.; Sanders, Gillian D.; Yancy, Clyde W.; Al-Khatib, Sana M.
Abstract : Background—: Clinical trials of implantable cardioverter defibrillators (ICDs) for primary prevention enrolled a limited number of women. We sought to examine clinical practice data to compare survival rates among women with heart failure with or without a primary prevention ICD. Methods and Results—: We linked data from 264 US hospitals included in the Get With The Guidelines for Heart Failure registry with data from the Centers for Medicare and Medicaid Services. From these sources, we propensity score matched 430 women with heart failure who received a primary prevention ICD to 430 women who did not; we further adjusted using a Cox proportional hazards model. Median follow-up was 3.4 and 3.0 years. For comparison, we matched 859 men receiving an ICD with 859 who did not; median follow-up was 3.9 versus 2.9 years. In the matched cohorts, an ICD was associated with similarly better survival in women (hazard ratio, 0.78; 95% confidence interval, 0.66–0.92; P =0.003) and men (hazard ratio, 0.76; 95% confidence interval, 0.67–0.87 P <0.001). There was no interaction between sex and presence of an ICD with respect to survival ( P =0.79). Conclusions—: Among patients with heart failure with reduced left ventricular ejection fraction, a primary prevention ICD was associated with a significant survival advantage among women and among men. These findings support guideline-directed use of primary prevention ICDs in eligible patients. Abstract : Supplemental Digital Content is available in the text.